Educating to Forgive as an Expression of Concern for Order in a Person’s Natural Environment. Part. 1: Evil and Harm in the Life of a Human Person and the Source of the Need to Forgive - Wyrostkiewicz, Michał (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The paper defines philosophical categories of good and evil in the process of upbringing and development of the personality. People are good by nature. That is why they tend towards the good, they desire what is good, they feel bad and do not function well when they are touched by evil. Goodness is part of the natural environment of the human being; goodness is the natural climate of the human person. At the same time, however, people perform bad deeds. They create evil. They often harm others. This is the cause of disorder in a person's environment. It turns out that the only effective and reasonable means of restoring such order is forgiveness. It is the only thing that has a chance to realistically stop the potential avalanche of evil that appears to be the obvious result of wrongdoing and “nurturing” harm or planning revenge. The evil that “insidiously” enters the world creates the need for forgiveness as the only way to respond to harm; as a way that leads to real order in a person's environment